Building a spectral cytometry toolbox: Coupling fluorescent proteins and antibodies to microspheres. Issue 10 (13th April 2022) - Monard, Simon
Abstract: Fluorescent proteins (FPs) have become an essential tool for biological research. Since the isolation and description of GFP, hundreds of fluorescent proteins have been discovered and created with various characteristics. The excitation of these proteins ranges from ultra‐violet (UV) up to near infra‐RED (NIR). Using conventional cytometry with each detector assigned to each fluorochrome, great care must be taken when selecting the optimal bandpass filters to minimalize the spectral overlap. In the last 8 years, several companies have released full spectrum flow cytometers which eliminates the need to change optical filters for analyzing FPs. This addressed at least part of the problem however, the laser wavelengths in commercial instruments are generally not ideal for all fluorescent proteins yet do allow the separation of at least six FPs. Another technical challenge is to have convenient single color controls. If four different FPs are being used in an experiment, single color controls will be needed to compensate or unmix the data. In the case of cultured cells this will involve having each of the FPs expressed in cell lines separately with a parental cell line expressing none. In the case of in vivo experiments, colonies of animals may need to be maintained expressing each FP along with a wildtype animal. This represents a considerable expense and inconvenience. An appealing alternative is to produce and purify FPs and covalently couple to polystyrene microspheres. Such microspheres are ready to use and can be stored at 4°C for months or even years without any deterioration in fluorescence. The same procedure can be used to couple antibodies to these particles. Here we describe this procedure which can be executed in any lab without any special equipment or skills.